(untitled) (Bangladesh Medical Journal, 2017)
Terminalia Chebula extract is used for regeneration of hepatic cells and protection of liver against damage due to its active component. This study aims to observe the protective effect of Terminalia Chebula against Paracetamol induced change of serum total protein level in Wister Albino rats. The study was carried out in the Department of Physiology, Dhaka Medical College (DMC) during January 2013 to December 2013. A total number of 44 rats, age ranging from 90 to 120 days, weight between 150 to 200 gm (initial body weight) were selected for the study. After acclimatization for 14 days, they were divided into control groups and experimental groups. Before sacrifice, final body weights of all the rats were measured. then all the rats were sacrificed on 22nd day and then blood samples were collected. For assessment of liver function, serum total protein level was done by using standard laboratory kits. The mean serum total protein level was significantly (p<0.001) lower in paracetamol treated control group in comparison to those of baseline control group. Serum total protein level of all experimental groups were significantly (P<0.001) higher than Paracetamol treated control group. From the results of this study, it may be concluded that Terminalia Chebula may have some protective effect against Paracetamol induced liver damage in rats. Bangladesh Med J. 2017 Jan; 46 (1): 11-14